Effects of starvation on the fighting ability of invasive and autochthonous ants. Issue 1 (15th December 2022) - Frizzi, Filippo; Balzani, Paride; Frasconi Wendt, Clara; Masoni, Alberto; Carta, Elisa; Innocenti, Maria Rita; Santini, Giacomo
Abstract: Ants are widespread in all terrestrial habitats, and competitive interactions between species are common. Although redistribution of food within a colony may buffer the negative effects of temporary resource shortages, colony functionality can be compromised when famine is prolonged. One of the possible effects of famine is impairment of the fighting ability of species, with cascade effects on community. Here, we investigated whether food shortage alters the fighting ability of workers of three dominant species in the Mediterranean area: the invasive alien species, Lasius neglectus and Linepithema humile, and one highly polydomous autochthonous species belonging to the Tapinoma nigerrimum complex. We performed laboratory tests of interspecific one‐on‐one aggression and pairwise group contests between species, with all possible combinations of artificially satiated and starved groups. Results showed that starvation had a scarce effect on the individual aggressiveness in all three species. Similarly, the outcomes of the group fights were only lightly affected, but with an important exception. The positions of species in the fighting hierarchies were in most cases clear and linear, with L. neglectus at the top. However, we found that L. humile and L. neglectus showed equal mortality when one of the two species was starved and the other satiated. Although we investigated only one aspect of competition, that is, fighting ability, our results provide a piece of the complex jigsaw of competitive interactions of ants, and suggest that food deprivation can be a determinant that alters the relationships between ants and promotes or hampers the coexistence of dominant species. Abstract : We investigated if food deprivation can alter individual aggressiveness and mortality rates during interspecific group fights between three dominant ant species in the Mediterranean area, two invasives, Linepithema humile and Lasius neglectus, and one autochthonous, Tapinoma nigerrimum. Despite the low effect on individual aggressiveness, group combats showed that starvation can alter the transitivity of competition among species.